Effect of sintering duration on the dielectric properties of 0.9BaTiO3–0.1CaCu3Ti4O12 nanocomposite synthesized by solid state route - Khare A.; Yadava S.S.; Mandal K.D.; Mukhopadhyay N.K. (My University, 2025)
A nanocomposite ceramic with the composition close to 0.9BaTiO3–0.1CaCu3Ti4O12 (BTC) was synthesized using a solid state method through sintering at 950 °C for different time durations 3, 6, 9 and 12 h. The structural and microstructural details were studied by X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM) techniques. XRD analysis confirmed the existence of BaTiO3 (BTO) and CaCu3Ti4O12 (CCTO) as the primary phases along with CuO and CaTiO3 as the minor aspects. The average grain sizes obtained by SEM analysis were found to be around 269 nm, 309 nm, 342 nm, and 734 nm for sintering durations 3, 6, 9 & 12 h respectively. TEM analysis showed the particle size in the range of 30 ± 10 nm. The surface morphology was analyzed by atomic force microscopy (AFM). The sample sintered for 3 h exhibited very high dielectric constant (ɛr ~ 319,674) at 1 kHz and 328 K. The presence of semiconducting grains with the insulating grain boundaries significantly attributes to such a high dielectric constant value, supporting the internal barrier layer capacitance (IBLC) mechanism operative in BTC nanocomposite. © 2016